A real-world study: third-line treatment options for metastatic colorectal cancer - Wu, Chen; Li, Shuai; Hou, Xinfang (Frontiers in Oncology, 2024)
BackgroundNumerous third-line treatment options exist for colorectal cancer. This study aims to assess the efficacy and safety of third-line therapies, including TKIs (fruquintinib, regorafenib) combined with PD-1 inhibitors, and trifluridine/tipiracil combined with bevacizumab, in patients with refractory microsatellite stable metastatic colorectal cancer who have progressed or are intolerant following standard first- and second-line treatments.Materials and methodsThis retrospective analysis collected data from patients with microsatellite stable advanced colorectal adenocarcinoma, diagnosed through histopathology and treated at Henan Provincial Cancer Hospital from May 2019 to April 2023. We compared the efficacy and safety of fruquintinib combined with PD-1 inhibitors, regorafenib combined with PD-1 inhibitors, and trifluridine/tipiracil combined with bevacizumab.ResultsAmong 60 eligible patients with refractory microsatellite stable metastatic colorectal adenocarcinoma, 29 (48.3%) received fruquintinib combined with PD-1 inhibitors, 15 (25%) received regorafenib combined with PD-1 inhibitors, and 16 (26.7%) received trifluridine/tipiracil combined with bevacizumab. The average follow-up period was 12.6 months (ranging from 2.3 to 37.6 months). After third-line treatment, the overall objective response rate (ORR) was 8.6%, and the disease control rate (DCR) was 78.6%. The median overall survival (OS) for the regorafenib, fruquintinib, and trifluridine/tipiracil groups was 19.2 months, 14.0 months, and 16.2 months, respectively, with no statistically significant differences observed. However, there were statistically significant differences in progression-free survival (PFS); the median PFS for the regorafenib group was 6.3 months, for the fruquintinib group was 4.2 months, and for the trifluridine/tipiracil group was 5.4 months. Pairwise comparisons indicated that the PFS for the regorafenib group was similar to that for the trifluridine/tipiracil group, both of which were superior to the fruquintinib group. Cox univariate regression analysis revealed that the presence of liver and peritoneal metastases was associated with PFS in third-line treatment.ConclusionIn the third-line treatment of colorectal cancer, regorafenib combined with PD-1 inhibitors and trifluridine/tipiracil combined with bevacizumab showed superiority over fruquintinib combined with PD-1 inhibitors in terms of PFS, but no statistically significant difference in OS was noted among the three groups.